RELATIONSHIP BETWEEN CERVICAL SAGITTAL ALIGNMENT AND CURVE PATTERN IN IDIOPATHIC SCOLIOSIS - Mauricio Coelho Lima; Marcelo Italo Risso Neto; Paulo Tadeu Maia Cavali; Samuel Henrique Jakoski Gehhlen; André Frazão Rosa; Sylvio Mistro Neto; Rafael Magalhães Grana; Alexander Junqueira Rossato; Maurício Antonelli Lehoczki; Alberto Cliquet Junior (Coluna/Columna)
ABSTRACT Objective: The aim of this study was to correlate the different curve patterns presented in idiopathic scoliosis with the sagittal cervical parameters of patients with this pathology. Method: This was a cross-sectional, descriptive and retrospective study. Information was collected from medical records and lateral panoramic radiographs of 49 patients with idiopathic scoliosis were analyzed. The data was assessed quantitatively using the following cervical parameters: Cobb from C2-C7, the distance from the center of gravity of the head to C7, the T1 slope, the thoracic Inlet angle, the cervical version, C7-S1 SVA, the Cobb angle of the main curve, and the kyphosis at T1-T12. These parameters were analyzed in relation to the different curve types presented and the lumbar and sagittal modifiers, as described by Lenke’s classification for idiopathic scoliosis. All the results were statistically analyzed and the significance level adopted was 5% (p<0.05). Results: The Cobb C2-C7 values showed a decrease in cervical lordosis in these patients (p = 0.048) and also showed an inverse relationship with thoracic kyphosis (p = 0.027). There was a statistically significant relationship between T1 inclination and loss of cervical lordosis (p = 0.003) also with variations in the sagittal modifier (p < 0.05). Lenke 2 and Lenke 4 curves were related to loss of cervical lordosis (p = 0.038). Conclusion: There was a loss of cervical lordosis in the patients in this study, evidenced by the alteration of the cervical sagittal parameters in these patients. The T1 slope was the variable that showed the greatest correlation with cervical alignment parameters, varying mainly in relation to the type of curve and sagittal modifier. In addition, curves affecting the upper thoracic spine (Lenke 2 and Lenke 4) significantly altered the sagittal cervical alignment of patients with idiopathic scoliosis, and it is recommended that they be carefully observed. Level of Evidence VI; Retrospective Observational Study.